E-Learning berbasis Moodle Mata Pelajaran Informatika dengan Pendekatan Project Based Learning - Sidiq, Erda Kurniawan; Wantoro , Jan (Jurnal Pendidikan Informatika (EDUMATIC), 2024)
The ppt learning delivery method for explaining lessons is considered less interesting and sometimes boring, plus project lessons are still conventional which can only be done in class. This research aims to create e-learning media with a project-based learning (PJBL) model for informatics lessons in vocational schools at Sukoharjo student park. This type of research is development by building or creating Moodle-based learning media. The method used in this research is the R&D method using the ADDIE model with only the Analysis, Design, and Implementation stages. Observations and questionnaires were used for the data collection process. The data analysis technique used is descriptive analysis in the form of percentage validity tests. The results of our findings are to produce e-learning to support students in implementing the PJBL learning approach in the classroom. Test results show that all system functionality functions well. This system makes the learning process using PJBL in the classroom more flexible and can be accessed from anywhere, increases collaboration between students virtually, and utilizes technology to present more interactive and interesting learning material.